The Role of Philosophy of Science in Scientific Advancement: A Systematic Literature Review - Helita, Helita; Sari, Ice Linsa; Septemi, Yulia; Yadi, Supri; Elisti, Yesmi (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2025)
This study explored the role of the Philosophy of Science in scientific as the foundation for the advancement and development of scientific knowledge, particularly in addressing life’s problems that cannot be solved by empirical science alone. The research employs a Systematic Literature Review (SLR) approach to collect and analyze data from research articles, scientific journals, and relevant books that discuss the development and interrelation between philosophy and science. The review findings indicate that the Philosophy of Science plays a crucial role in bridging the gap between philosophical inquiry and scientific practice. It continues to grow within its boundaries while maintaining its essence as a source of radical criticism and substantial reasoning. The study highlights that philosophy serves as a critical dialogue partner for science, offering reflective insights that help scientists understand and refine their methodologies and theoretical assumptions. This study emphasizes the balanced position of philosophy among the sciences, showing its relevance not only as a theoretical discipline but also as an integral element in shaping the direction and ethics of scientific progress. This research contributes to a deeper understanding of how philosophical reflection enhances the autonomy and specificity of science, reaffirming the significance of the Philosophy of Science as both a foundation and a guide in the evolution of scientific thought.